Literature Database CIAT FAO - Castro-Nuñez, Augusto Carlos; Sylvester, Janelle Marie; Gutiérrez, Diana; Pérez Marulanda, Lisset; Vanegas Cubillos, Martha Cristina; Castro-Llanos, Fabio Alexander (2022)
Literature database from systematic bibliographic review to identify underlying drivers of deforestation in tropical countries/regions